Dehumidifying method of moisture absorption sulfate-based positive electrode material

By mixing the hygroscopic sulfate base material and gas making in the inert atmosphere, the problem of hygroscopic sulfate base material is difficult to dehydrate, and the effect of good dehydration, simple craftsmanship, and low cost are achieved. The electrochemical performance of the material is restored.

CN119353878AInactive Publication Date: 2025-01-24HUNAN NANENG TIMES TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411553469.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-02
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There has been no reported method for effectively dehumidifying the hygroscopic sulfate-based positive electrode material in the prior art, resulting in large differences in the air stability, actual specific capacity and cycle stability of the material, affecting the material's ideal electrochemical performance.

Method used

By mixing the moisturizing sulfate base material and the gas -making agent evenly, the heat treatment is performed in an inert atmosphere, and it can be cooled to the room temperature with the furnace to get dehydrated sulfate bases. In the case of heating, gas that does not react with the iconic material of sodium sulfate sodium sulfate can enter the medium and micropores to promote the water molecules from the surface of the material.

Benefits of technology

It achieves good dehumidification effect, simple process, high feasibility, low cost, and is suitable for industrial application. The obtained dehumidified sulfate-based cathode material has a stable crystal structure, and the assembled battery has high discharge specific capacity and stable cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119353878A_ABST
    Figure CN119353878A_ABST
Patent Text Reader

Abstract

A dehumidification method of a moisture-absorbing sulfate-based positive electrode material comprises the following steps: uniformly mixing the moisture-absorbing sulfate-based positive electrode material with a gas-making agent, carrying out heat treatment in an inert atmosphere, and cooling to room temperature along with a furnace to obtain the dehumidified sulfate-based positive electrode material. The method is good in dehumidification effect, simple in process, high in feasibility, low in cost and suitable for industrial application, the obtained dehumidified sulfate-based positive electrode material and a sulfate-based positive electrode material before moisture absorption are consistent in crystal and stable in crystal structure, and an assembled battery is high in specific discharge capacity and stable in cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a dehumidification method for a positive electrode material, in particular to a dehumidification method for a hygroscopic sulfate-based positive electrode material. Background Art

[0002] Sodium-ion batteries have the advantages of high abundance of raw materials, low cost, and environmental friendliness. In addition to lithium-ion batteries, they are the most widely studied and applied cathode materials. Among the many cathode materials that have been reported, polyanion cathode materials have been widely studied due to their advantages such as stable structure, high working voltage, and no risk of gas production. Compared with phosphate and pyrophosphate, sulfate has higher electronegativity and stronger inductive effect. Therefore, sulfate cathode materials have higher working voltages. In particular, iron-based polyanion compounds, represented by sodium ferrous sulfate, have become one of the research hotspots in recent years because of their cheap raw materials, good cycle stability, and high working voltage. However, sulfate-based cathode materials have problems such as easy water absorption, which leads to large differences in the air stability, actual specific capacity, and cycle stability of the materials, affecting the ideal electrochemical performance of the materials.

[0003] At present, there is no reported method for effectively dehumidifying hygroscopic sulfate-based positive electrode materials in the prior art. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for dehumidifying hygroscopic sulfate-based positive electrode material with good dehumidification effect, simple process, high feasibility, low cost, and suitability for industrial application. The obtained dehumidified sulfate-based positive electrode material has the same crystal structure as the sulfate-based positive electrode material before moisture absorption, has a stable crystal structure, and the assembled battery has a high discharge specific capacity and stable cycle performance.

[0005] The technical solution adopted by the present invention to solve its technical problem is as follows: a dehumidification method for a hygroscopic sodium ferrous sulfate positive electrode material, the hygroscopic sulfate-based positive electrode material is uniformly mixed with a gas-generating agent, heat-treated under an inert atmosphere, and cooled to room temperature with the furnace to obtain a dehumidified sulfate-based positive electrode material.

[0006] The inventive idea of ​​the method of the present invention is: when there are mesopores and micropores on the surface interface of the hygroscopic sodium ferrous sulfate positive electrode material, due to the large interaction force between the solid and the liquid, water molecules are trapped and it is difficult to escape and leave the surface of the material even when heated. After the gas generating agent is added and mixed with the hygroscopic sodium ferrous sulfate positive electrode material, the gas generating agent generates gas that does not react with the hygroscopic sodium ferrous sulfate positive electrode material under heating, and can enter the mesopores and micropores to promote the water molecules to leave the surface of the material at the surface interface.

[0007] Preferably, the amount of the gas generating agent is 0.1-5.0% (more preferably 0.5-3.0%) of the mass of the hygroscopic sulfate-based positive electrode material. If the amount of the gas generating agent added is too small, the gas generated is small and it is difficult to achieve the gas generating effect. However, the amount added should not be too high, otherwise too many residual byproducts will be generated, affecting the electrochemical performance.

[0008] Preferably, the gasifier includes one or more of glucose, sucrose, ascorbic acid, citric acid, sodium bicarbonate, sodium acetate, sodium oxalate or ammonium carbonate, etc. The main principle of the gasifier is that the gasifier will decompose during the heating process at a specific temperature to produce gases that do not react with the sulfate-based positive electrode material. These gases can penetrate into the micropores of the hygroscopic sulfate-based positive electrode material and promote the escape of water molecules, thereby obtaining a dehumidified sulfate-based positive electrode material and restoring the original electrochemical properties.

[0009] Preferably, the hygroscopic sulfate-based positive electrode material before and after moisture absorption comprises a sulfate-based positive electrode material having a molecular formula of A 2+2x M 2-x (SO 4 ) 3 Compounds and carbon-coated materials thereof, wherein 0≤x≤0.3. More preferably, the sulfate-based positive electrode material comprises a compound having a molecular formula of Na 2+2x Fe 2-x (SO 4 ) 3 Compounds and carbon-coated materials thereof, wherein 0≤x≤0.3.

[0010] Preferably, the hygroscopic sulfate-based cathode material comprises a molecular formula A 2 M(SO 4 ) 2 ·yH 2 O crystalline hydrate and carbon coating material thereof, wherein 1≤y≤9. More preferably, the hygroscopic sulfate-based positive electrode material comprises a molecular formula of Na 2 Fe(SO 4 ) 2 ·yH 2 O compound and carbon-coated material thereof, wherein 1≤y≤4.

[0011] Preferably, the moisture content of the hygroscopic sulfate-based cathode material is 1 to 30% (more preferably 2 to 20%). If the moisture content is too high, the gas-generating agent will react with the water easily after being added, and the gas-generating effect will be lost, and the purpose of dehumidification cannot be achieved. More preferably, when the hygroscopic sulfate-based cathode material contains a molecular formula of Na 2 Fe(SO 4 ) 2 ·yH 2 O compounds and their carbon-coated materials, the water content is 3.6 to 13.9%.

[0012] Preferably, in the molecular formula of the sulfate-based cathode material or the hygroscopic sulfate-based cathode material, A represents Na or Li, and M represents a divalent transition metal. More preferably, the divalent transition metal includes one or more of Fe, Co, Mn, Ni or Zn.

[0013] Preferably, the morphology of the hygroscopic sulfate-based cathode material is micron-shaped spherical or fragment-shaped particles and agglomerates thereof.

[0014] Preferably, the particle size of the hygroscopic sulfate-based positive electrode material ranges from 1 to 50 μm. When positive electrode materials of different particle sizes are mixed, they can fill the gaps between particles and enhance their conductivity.

[0015] Preferably, the mixing method includes grinding, sand milling or ball milling, etc. The mixing is achieved by mechanical force, shear force and other principles. During the mixing process, it is beneficial for the gas generating agent to fully contact and react with the surface interface of the hygroscopic sulfate-based positive electrode material, which is more conducive to the subsequent heat treatment dehumidification reaction.

[0016] Preferably, the mixing speed is 120-180 r / min and the mixing time is 1-10 min. Under the above conditions, it is conducive to uniform mixing of the hygroscopic sulfate positive electrode material and the gas generating agent.

[0017] Preferably, the heat treatment refers to: heating from room temperature to 100-400°C (more preferably 200-350°C) at a rate of 1-10°C / min (more preferably 2-8°C / min), and then keeping the temperature for 1-24h (more preferably 1-12h). During the heat treatment process, the gasifier is gradually decomposed as the temperature rises, generating gas that does not react with the hygroscopic sulfate positive electrode material, while taking away the water molecules on the surface of the positive electrode material. During the heat preservation stage, the gasifier is completely decomposed, so that the dehumidification reaction can be fully carried out to ensure the dehumidification effect. At the same time, the heat preservation stage is beneficial to A 2+2x M 2-x (SO 4 ) 3 recrystallization to ensure the integrity of the crystal structure.

[0018] Preferably, the inert atmosphere includes one or more of argon, helium or nitrogen. Sintering in an inert atmosphere can ensure that the sulfate-based positive electrode material is not oxidized and maintains ideal electrochemical properties. The protective atmosphere used in the present invention is a high-purity atmosphere with a purity of ≥99.9%.

[0019] The positive electrode sheet made of the dehumidified sulfate-based positive electrode material obtained by the dehumidification method is used to assemble button-type, cylindrical, square or soft-pack sodium ion batteries.

[0020] The beneficial effects of the method of the present invention are as follows: (1) The method of the present invention has a good dehumidification effect, which is consistent with the crystal structure of the sulfate-based positive electrode material before moisture absorption and has a stable crystal structure; (2) The battery assembled with the sodium ion battery positive electrode made of the dehumidified sodium ferrous sulfate positive electrode material obtained by the method of the present invention has a first charge specific capacity of 97.87 mAh / g, a first discharge specific capacity of 87.42 mAh / g, and a first coulombic efficiency of 89.32% at a charge and discharge voltage of 2.0 to 4.5 V and a rate of 0.1C (11 mA / g). The charge and discharge reaction is highly reversible. At a rate of 1C (110 mA / g, starting from the 4th cycle), the 4th cycle discharge specific capacity is 85.79 mAh / g, and the cycle is 100 cycles. The charge and discharge specific capacities after the cycle are 86.27mAh / g and 85.67mAh / g respectively, the coulombic efficiency is 99.30%, and the discharge specific capacity retention rate at the 100th cycle is still as high as 98.00%, indicating that the dehumidified sodium ferrous sulfate positive electrode material has excellent chemical sodium storage performance, high discharge specific capacity, and good cycle stability; the method of the present invention solves the shortcomings of low capacity and poor cycle stability of hygroscopic sulfate-based positive electrode materials, restores the original electrochemical activity of sulfate-based positive electrode materials, and enables sulfate-based positive electrode materials to be repeatedly used; (3) The method of the present invention has simple process, high feasibility, low raw material cost, and is suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The SEM images of the sodium ferrous sulfate positive electrode material (a), the hygroscopic sodium ferrous sulfate positive electrode material (b) obtained in Reference Example 1, and the dehumidified sodium ferrous sulfate positive electrode material (c) obtained in Example 1 of the present invention; Figure 2 XRD patterns of the sodium ferrous sulfate positive electrode material, the hygroscopic sodium ferrous sulfate positive electrode material obtained in Reference Example 1, and the dehumidified sodium ferrous sulfate positive electrode material obtained in Example 1 of the present invention; Figure 3 : is a thermogravimetric diagram of the dehumidified sodium ferrous sulfate positive electrode material obtained in Example 1 of the present invention and the dehumidified sodium ferrous sulfate positive electrode material obtained in Comparative Example 1; Figure 4 It is a first charge and discharge curve diagram of a battery assembled with electrodes made of a sodium ferrous sulfate positive electrode material, a hygroscopic sodium ferrous sulfate positive electrode material obtained in Reference Example 1, and a dehumidified sodium ferrous sulfate positive electrode material obtained in Example 1 of the present invention; Figure 5 It is a cycle curve diagram of a battery assembled with electrodes made of a sodium ferrous sulfate positive electrode material, a hygroscopic sodium ferrous sulfate positive electrode material obtained in Reference Example 1, and a dehumidified sodium ferrous sulfate positive electrode material obtained in Example 1 of the present invention; Figure 6 This is the first charge and discharge curve of a battery assembled with an electrode made of the dehumidified sodium ferrous sulfate positive electrode material obtained in Comparative Example 1 of the present invention; Figure 7 This is a cycle curve diagram of a battery assembled with an electrode made of the dehumidified sodium ferrous sulfate positive electrode material obtained in Comparative Example 1 of the present invention; In the figure, the sodium ferrous sulfate positive electrode material is referred to as NFS, the hygroscopic sodium ferrous sulfate positive electrode material is referred to as hygroscopic NFS, and the dehumidified sodium ferrous sulfate positive electrode material is referred to as dehumidified NFS. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with the embodiments and drawings.

[0023] The sodium ferrous sulfate positive electrode material Na used in the embodiments of the present invention and the comparative examples is 2.5 Fe 1.75 (SO 4 ) 3 purchased from Hunan NaNengShiDai Technology Development Co., Ltd.; the protective atmosphere used in the embodiments of the present invention and the comparative examples are all high-purity atmospheres with a purity of ≥99.9%; the raw materials or chemical reagents used in the embodiments of the present invention and the comparative examples, unless otherwise specified, are all obtained through conventional commercial channels.

[0024] Reference Example 1 for the preparation method of hygroscopic sodium ferrous sulfate positive electrode material Take 5g of sodium ferrous sulfate positive electrode material Na 2.5 Fe 1.75 (SO 4 ) 3 , exposed to air at an average temperature of 25°C and an average relative humidity of 75%RH for 6h, 5.69g of Na 2 Fe(SO 4 ) 2 ·4H 2 O of hygroscopic sodium ferrous sulfate cathode material.

[0025] like Figure 1 As shown in (a), before moisture absorption, the morphology of the sodium ferrous sulfate cathode material is micron-shaped spherical or fragmented particles and their agglomerates, with a particle size range of 5 to 45 μm, among which the particle sizes of D10, D50, and D90 are 6.814 μm, 18.644 μm, and 43.713 μm, respectively; Figure 1 As shown in (b), the morphology of the hygroscopic sodium ferrous sulfate positive electrode material obtained in this reference example is micron-shaped spherical or fragmented particles and their agglomerates, with a particle size range of 6 to 46 μm, among which the particle sizes of D10, D50, and D90 are 7.045 μm, 21.168 μm, and 45.336 μm, respectively; this indicates that the particle size of the sodium ferrous sulfate positive electrode material becomes larger after moisture absorption, and the moisture absorption process is that water molecules enter the surface interface of the material to form a mixed phase, and the volume expands.

[0026] like Figure 2As shown, before moisture absorption, the peak shape of the sodium ferrous sulfate positive electrode material is similar to that of Na 2.5 Fe 1.75 (SO 4 ) 3 The typical characteristic peaks in the standard card (PDF#97-025-2404) correspond one to one, indicating that the obtained sodium ferrous sulfate positive electrode material Na 2.5 Fe 1.75 (SO 4 ) 3 It is an ideal material without impurities; after moisture absorption, the crystal structure of the hygroscopic sodium ferrous sulfate positive electrode material obtained in this reference example has a new impurity peak, which means the appearance of impurity phase. 2 Fe(SO 4 ) 2 •4H 2 O standard card (PDF#97-019-4363) shows that this impurity phase is sodium ferrous sulfate crystals containing crystal water.

[0027] Reference Example 2 for the preparation method of hygroscopic sodium ferrous sulfate positive electrode material Take 5g of sodium ferrous sulfate positive electrode material Na 2.5 Fe 1.75 (SO 4 ) 3 , exposed to air at an average temperature of 25°C and an average relative humidity of 75%RH for 3h, 5.48g of Na-containing solution with a water content of 9.6% was obtained. 2 Fe(SO 4 ) 2 ·4H 2 O of hygroscopic sodium ferrous sulfate cathode material.

[0028] After testing, the morphology of the hygroscopic sodium ferrous sulfate positive electrode material obtained in this reference example is micron-shaped spherical or fragmentary particles and their agglomerates, with a particle size range of 6 to 45.5 μm, among which the particle sizes of D10, D50, and D90 are 6.345 μm, 20.234 μm, and 45.176 μm, respectively, indicating that the particle size of the sodium ferrous sulfate positive electrode material becomes larger after moisture absorption. The moisture absorption process is that water molecules enter the surface interface of the material to form a mixed phase, and the volume expands.

[0029] After testing, after moisture absorption, the crystal structure of the hygroscopic sodium ferrous sulfate positive electrode material obtained in this reference example showed a new impurity peak, which means the appearance of impurity phase. 2 Fe(SO 4 ) 2 •4H 2 O standard card (PDF#97-019-4363) shows that this impurity phase is sodium ferrous sulfate crystals containing crystal water.

[0030] Reference Example 3 for the preparation method of hygroscopic sodium ferrous sulfate positive electrode material Take 5g of sodium ferrous sulfate positive electrode material Na 2.5 Fe 1.75 (SO 4 ) 3 , exposed to air at an average temperature of 25°C and an average relative humidity of 75%RH for 1h, 5.27g of Na-containing solution with a water content of 5.4% was obtained. 2 Fe(SO 4 ) 2 ·4H 2 O of hygroscopic sodium ferrous sulfate cathode material.

[0031] After testing, the morphology of the hygroscopic sodium ferrous sulfate positive electrode material obtained in this reference example is micron-shaped spherical or fragmented particles and their agglomerates, with a particle size range of 5 to 45 μm, among which the particle sizes of D10, D50, and D90 are 5.541 μm, 19.203 μm, and 44.875 μm, respectively, indicating that the particle size of the sodium ferrous sulfate positive electrode material becomes larger after moisture absorption. The moisture absorption process is that water molecules enter the surface interface of the material to form a mixed phase, and the volume expands.

[0032] After testing, after moisture absorption, the crystal structure of the hygroscopic sodium ferrous sulfate positive electrode material obtained in this reference example showed a new impurity peak, which means the appearance of impurity phase. 2 Fe(SO 4 ) 2 •4H 2 O standard card (PDF#97-019-4363) shows that this impurity phase is sodium ferrous sulfate crystals containing crystal water.

[0033] A dehumidification method for hygroscopic sodium ferrous sulfate positive electrode material Example 1 5.69 g of the sodium-containing 2 Fe(SO 4 ) 2 ·4H 2 The hygroscopic sodium ferrous sulfate positive electrode material of O and 0.05g citric acid are ground and mixed for 5min at a rotation speed of 150r / min until uniform. The obtained mixed powder is placed in a corundum crucible and placed in a tubular furnace. In a high-purity argon atmosphere, the temperature is increased from room temperature to 250℃ at a rate of 3℃ / min, and then heat-treated for 1h. The mixture is cooled to room temperature with the furnace to obtain a dehumidified sulfate-based positive electrode material.

[0034] like Figure 1As shown in (c), the morphology of the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention is micron-shaped spherical or fragmentary particles and their agglomerates, with a particle size range of 5 to 45 μm, among which the particle sizes of D10, D50, and D90 are 5.677 μm, 18.018 μm, and 43.168 μm, respectively, indicating that the particle size of the dehumidified sodium ferrous sulfate positive electrode material obtained by the method of the present invention is almost the same as that of the sodium ferrous sulfate positive electrode material before moisture absorption, and the method of the present invention can basically remove the water molecules on the surface of the positive electrode material.

[0035] like Figure 2 As shown, after dehumidification treatment, the crystal structure of the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention is similar to that of Na 2.5 Fe 1.75 (SO4) 3 The typical characteristic peaks of the standard card (PDF#97-025-2404) perfectly match, that is, they are consistent with the crystal structure of the sodium ferrous sulfate cathode material before moisture absorption, indicating that after the dehumidification treatment of the method of the present invention, the crystal structure of the sodium ferrous sulfate cathode material is basically restored to its original state, thereby ensuring the stable electrochemical activity of the material; at the same time, there are no impurity peaks of citric acid, indicating that the added citric acid gasifier and its re-firing by-products do not affect the crystal structure of the dehumidified sodium ferrous sulfate cathode material.

[0036] like Figure 3 As shown, the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention is subjected to thermogravimetric analysis. When heated from room temperature to 300°C, its weight loss rate is extremely low, indicating that after adding the gas generating agent, the crystal water in the hygroscopic sodium ferrous sulfate positive electrode material can be more completely removed.

[0037] In order to test the electrochemical properties of the sodium ferrous sulfate positive electrode material before and after moisture absorption and dehumidification, the positive electrode sheets made of the sodium ferrous sulfate positive electrode material, the hygroscopic sodium ferrous sulfate positive electrode material obtained in Reference Example 1, and the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention according to the following methods were used to assemble button-type sodium ion batteries.

[0038] The preparation method of the positive electrode plate is as follows: weigh 0.8 g of the dehumidified sodium ferrous sulfate positive electrode material obtained in Example 1 of the present invention, add 0.1 g of conductive carbon black SP as a conductive agent and 0.1 g of PVDF polyvinylidene fluoride as a binder, and use N-methylpyrrolidone as a solvent, mix and grind to obtain the positive electrode material.

[0039] The battery assembly method is as follows: the positive electrode material is coated on the surface of aluminum foil to form an electrode sheet, and then, in a closed glove box filled with an inert atmosphere, the electrode sheet is used as the positive electrode, the metal sodium sheet is used as the negative electrode, the glass fiber membrane is used as the separator, and 1 mol / L NaClO 4 / EC:DMC (volume ratio 1:1) containing 5.0% FEC as the electrolyte was assembled into CR2032 button cells for charge and discharge tests.

[0040] like Figure 4 As shown, the sodium ferrous sulfate cathode material has a first charge and discharge specific capacity of 97.31 mAh / g and 88.88 mAh / g at a charge and discharge voltage of 2.0-4.5 V and a rate of 0.1 C (11 mA / g), and a coulombic efficiency of 91.34%. The hygroscopic sodium ferrous sulfate cathode material obtained in Reference Example 1 has a charge and discharge voltage of 2.0 to 4.5 V and a rate of 0.1 C (11 mA / g). The first charge and discharge specific capacities are 51.08 mAh / g and 35.12 mAh / g, respectively, and the coulombic efficiency is only 68.75%. The dehumidified sodium ferrous sulfate cathode material obtained in the embodiment of the present invention has a first charge and discharge specific capacity of 93.92 mAh / g and 85.44 mAh / g at a charge and discharge voltage of 2.0 to 4.5 V and a rate of 0.1 C (11 mA / g), and a Coulombic efficiency of up to 90.97%. The results show that after the sodium ferrous sulfate positive electrode material absorbs moisture, its charge and discharge performance decreases significantly. The electrochemical performance of the sodium ferrous sulfate positive electrode material after dehumidification treatment by the method of the present invention is mostly restored, close to the sodium ferrous sulfate positive electrode material before moisture absorption, indicating that the dehumidification effect of the method of the present invention is significant.

[0041] like Figure 5 As shown, the sodium ferrous sulfate cathode material has a discharge capacity of 87.50 mAh / g from the 4th cycle at a charge and discharge voltage of 2.0 to 4.5 V and a rate of 1C (110 mA / g). After 100 cycles, the charge and discharge capacities are 85.57 mAh / g and 84.8 mAh / g, respectively. The coulombic efficiency is 99.10%, and the discharge capacity retention rate at the 100th cycle is 95.41%. The hygroscopic sodium ferrous sulfate cathode material obtained in Reference Example 1 has a discharge capacity of 28.78 mAh / g from the 4th cycle at a charge and discharge voltage of 2.0 to 4.5 V and a rate of 1C (110 mA / g). The charge and discharge capacities after 100 cycles are 27.99 mAh / g and 27.28 mAh / g, respectively, and the coulombic efficiency is 97.46%. The discharge capacity retention rate at the 100th cycle is only 77.68%. The dehumidified sodium ferrous sulfate cathode material obtained in the embodiment of the present invention has a discharge capacity of 83.76 mAh / g from the 4th cycle at a charge and discharge voltage of 2.0 to 4.5 V and a rate of 1C (110 mA / g). The charge and discharge capacities after 100 cycles are 83.72 mAh / g and 82.84 mAh / g, respectively. The coulombic efficiency is 98.95%, and the discharge capacity retention rate at the 100th cycle is still as high as 96.96%. The results show that after the sodium ferrous sulfate positive electrode material absorbs moisture, its cycle performance decreases significantly and the capacity retention rate is seriously reduced. The cycle performance of the sodium ferrous sulfate positive electrode material after dehumidification treatment by the method of the present invention can be effectively restored, close to the sodium ferrous sulfate positive electrode material before moisture absorption, indicating that the dehumidification treatment of the method of the present invention can restore its original crystal structure, and can maintain structural stability during the charge and discharge process, with small volume expansion and good conductivity, making the charge and discharge reaction highly reversible.

[0042] Example 2 of a dehumidification method for a hygroscopic sodium ferrous sulfate positive electrode material 5.48 g of the sodium-containing 2 Fe(SO 4 ) 2 ·4H 2 The hygroscopic sodium ferrous sulfate positive electrode material of O and 0.055g sodium oxalate are ground and mixed at a rotation speed of 170r / min for 8min until uniform. The obtained mixed powder is placed in a corundum crucible and placed in a tubular furnace. In a high-purity nitrogen atmosphere, the temperature is increased from room temperature to 300°C at a rate of 5°C / min, and then heat-treated for 2h. The mixture is cooled to room temperature with the furnace to obtain a dehumidified sulfate-based positive electrode material.

[0043] After testing, the morphology of the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention is micron-shaped spherical or fragmentary particles and their agglomerates, with a particle size range of 5 to 45 μm, among which the particle sizes of D10, D50, and D90 are 5.843 μm, 19.324 μm, and 44.563 μm, respectively, indicating that the particle size of the dehumidified sodium ferrous sulfate positive electrode material obtained by the method of the present invention is almost the same as that of the sodium ferrous sulfate positive electrode material before moisture absorption, and the method of the present invention can basically remove the water molecules on the surface of the positive electrode material.

[0044] After testing, after dehumidification treatment, the crystal structure of the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention is similar to that of Na 2.5 Fe 1.75 (SO 4 ) 3The typical characteristic peaks of the standard card (PDF#97-025-2404) perfectly match, that is, they are consistent with the crystal structure of the sodium ferrous sulfate positive electrode material before moisture absorption, indicating that after the dehumidification treatment of the method of the present invention, the crystal structure of the sodium ferrous sulfate positive electrode material is basically restored to its original state, thereby ensuring the stable electrochemical activity of the material; at the same time, there is no impurity peak of sodium oxalate, indicating that the added sodium oxalate gasifier and its re-firing by-products do not affect the crystal structure of the dehumidified sodium ferrous sulfate positive electrode material.

[0045] In order to test the electrochemical performance of the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention, the positive electrode sheet prepared according to the following method was used to assemble a button-type sodium ion battery.

[0046] The preparation method of the positive electrode plate is the same as that of Example 1.

[0047] The battery assembly method is the same as in Example 1.

[0048] After testing, the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention has a first charge and discharge specific capacity of 95.83mAh / g and 86.92mAh / g respectively at a charge and discharge voltage of 2.0-4.5V and a rate of 0.1C (11mA / g), and the coulombic efficiency is still as high as 90.70%; the results show that the electrochemical properties of the sodium ferrous sulfate positive electrode material after dehumidification treatment by the method of the present invention are mostly restored, close to the sodium ferrous sulfate positive electrode material before moisture absorption, indicating that the dehumidification effect of the method of the present invention is remarkable.

[0049] After testing, the dehumidified sodium ferrous sulfate cathode material obtained in the embodiment of the present invention has a discharge capacity of 83.43 mAh / g from the 4th cycle at a charge and discharge voltage of 2.0 to 4.5 V and a rate of 1C (110 mA / g). The charge and discharge capacities after 100 cycles are 83.21 mAh / g and 81.97 mAh / g, respectively, and the coulomb efficiency is 98.51%. The discharge capacity retention rate at the 100th cycle is still as high as 94.31%. The results show that the cycle performance of the sodium ferrous sulfate positive electrode material after dehumidification treatment by the method of the present invention can be effectively restored, close to the sodium ferrous sulfate positive electrode material before moisture absorption, indicating that the dehumidification treatment of the method of the present invention can restore its original crystal structure and maintain structural stability during the charge and discharge process, with small volume expansion and good conductivity, making the charge and discharge reaction highly reversible.

[0050] Example 3 of a dehumidification method for a hygroscopic sodium ferrous sulfate positive electrode material 5.27 g of the sodium-containing 2 Fe(SO 4 ) 2 ·4H 2The hygroscopic sodium ferrous sulfate positive electrode material of O and 0.05g glucose were ground and mixed at a rotation speed of 130r / min for 4min until uniform. The obtained mixed powder was placed in a corundum crucible and placed in a tubular furnace. In a high-purity argon atmosphere, the temperature was raised from room temperature to 350℃ at a rate of 8℃ / min, and then heat-treated for 3h. The mixture was cooled to room temperature with the furnace to obtain a dehumidified sulfate-based positive electrode material.

[0051] After testing, the morphology of the dehumidified sodium ferrous sulfate positive electrode material obtained in this embodiment is micron-shaped spherical or fragmentary particles and their agglomerates, with a particle size range of 5 to 44 μm, among which the particle sizes of D10, D50, and D90 are 5.245 μm, 18.138 μm, and 43.216 μm, respectively, indicating that the particle size of the dehumidified sodium ferrous sulfate positive electrode material obtained by the method of the present invention is almost the same as that of the sodium ferrous sulfate positive electrode material before moisture absorption, and the method of the present invention can basically remove the water molecules on the surface of the positive electrode material.

[0052] After testing, after dehumidification treatment, the crystal structure of the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention is similar to that of Na 2.5 Fe 1.75 (SO4) 3 The typical characteristic peaks of the standard card (PDF#97-025-2404) perfectly match, that is, they are consistent with the crystal structure of the sodium ferrous sulfate cathode material before moisture absorption, indicating that after the dehumidification treatment of the method of the present invention, the crystal structure of the sodium ferrous sulfate cathode material is basically restored to its original state, thereby ensuring the stable electrochemical activity of the material; at the same time, there is no impurity peak of glucose, indicating that the added glucose gasifier and its re-firing by-products do not affect the crystal structure of the dehumidified sodium ferrous sulfate cathode material.

[0053] In order to test the electrochemical performance of the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention, the positive electrode sheet prepared according to the following method was used to assemble a button-type sodium ion battery.

[0054] The preparation method of the positive electrode plate is the same as that of Example 1.

[0055] The battery assembly method is the same as in Example 1.

[0056] After testing, the dehumidified sodium ferrous sulfate positive electrode material obtained in the embodiment of the present invention has a first charge and discharge specific capacity of 97.87mAh / g and 87.42mAh / g respectively at a charge and discharge voltage of 2.0-4.5V and a rate of 0.1C (11mA / g), and the coulombic efficiency is still as high as 89.32%; the results show that the electrochemical properties of the sodium ferrous sulfate positive electrode material after dehumidification treatment by the method of the present invention are mostly restored, close to the sodium ferrous sulfate positive electrode material before moisture absorption, indicating that the dehumidification effect of the method of the present invention is remarkable.

[0057] After testing, the dehumidified sodium ferrous sulfate cathode material obtained in the embodiment of the present invention has a discharge capacity of 85.79 mAh / g from the 4th cycle at a charge and discharge voltage of 2.0 to 4.5 V and a rate of 1C (110 mA / g). The charge and discharge capacities after 100 cycles are 86.27 mAh / g and 85.67 mAh / g, respectively, and the coulomb efficiency is 99.30%. The discharge capacity retention rate at the 100th cycle is still as high as 98.00%. The results show that the cycle performance of the sodium ferrous sulfate positive electrode material after dehumidification treatment by the method of the present invention can be effectively restored, close to the sodium ferrous sulfate positive electrode material before moisture absorption, indicating that the dehumidification treatment of the method of the present invention can restore its original crystal structure and maintain structural stability during the charge and discharge process, with small volume expansion and good conductivity, making the charge and discharge reaction highly reversible.

[0058] Comparative Example 1 5.69 g of the sodium-containing 2 Fe(SO 4 ) 2 ·4H 2 The hygroscopic sodium ferrous sulfate positive electrode material of O was ground at a rotation speed of 150r / min for 5min until it was uniform, then placed in a corundum crucible and placed in a tubular furnace. In a high-purity argon atmosphere, the temperature was raised from room temperature to 200°C at a rate of 5°C / min, and then heat-treated for 1h. The material was cooled to room temperature with the furnace to obtain a dehumidified sulfate-based positive electrode material.

[0059] After testing, the morphology of the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention is micron-shaped spherical or fragmentary particles and agglomerates thereof, with a particle size range of 6 to 45 μm, wherein the particle sizes of D10, D50, and D90 are 6.362 μm, 20.025 μm, and 44.762 μm, respectively, that is, the particle size of the dehumidified sodium ferrous sulfate positive electrode material obtained by the comparative example of the present invention is between the particle size of the sodium ferrous sulfate positive electrode material before and after moisture absorption, indicating that after the dehumidification treatment of the comparative example of the present invention, the water molecules on the surface of the positive electrode material cannot be completely removed.

[0060] After testing, after dehumidification treatment, the crystal structure of the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention is similar to that of Na 2.5 Fe 1.75 (SO4) 3 Most of the typical characteristic peaks of the standard card (PDF#97-025-2404) can be matched one by one, that is, they are consistent with the crystal structure of the sodium ferrous sulfate positive electrode material before moisture absorption, but there is a weak peak that can be matched with Na 2 Fe(SO 4 ) 2 •4H 2The impurity peaks matched with the O standard card (PDF#97-019-4363) indicate that the degassing agent was not used for dehumidification treatment and the dehumidification effect could not be completely achieved.

[0061] like Figure 3 As shown, the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention and Example 1 of the present invention was subjected to thermogravimetric analysis under the same conditions. When heated from room temperature to 300°C, the loss rate of the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention was still as high as 7%, indicating that due to the absence of the addition of the aerator, the crystal water in the hygroscopic sodium ferrous sulfate positive electrode material cannot be more completely removed.

[0062] The positive electrode sheet made of the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention is used to assemble a button-type sodium ion battery.

[0063] The preparation method of the positive electrode plate is the same as that of Example 1.

[0064] The battery assembly method is the same as in Example 1.

[0065] like Figure 6 As shown, the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention has a charge and discharge voltage of 2.0 to 4.5 V and a rate of 0.1 C (11 mA / g), and the first charge and discharge specific capacities are 75.47 mAh / g and 68.45 mAh / g, respectively, and the coulombic efficiency is 90.70%; the results show that the dehumidified sodium ferrous sulfate positive electrode material of the comparative example of the present invention is directly sintered without adding a gas generating agent, and although its electrochemical properties can be partially restored, they are far worse than the electrochemical properties of the sodium ferrous sulfate positive electrode material before moisture absorption and obtained in Example 1 of the present invention, indicating that the dehumidification treatment in the absence of a gas generating agent cannot achieve the effect of complete dehumidification, and Na 2 Fe(SO 4 ) 2 •4H 2 O crystal hydrate, affecting the effective performance of electrochemical activity.

[0066] like Figure 7 As shown, the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention has a discharge specific capacity of 65.18 mAh / g from the 4th cycle under a charge and discharge voltage of 2.0 to 4.5 V and a 1C rate (110 mA / g). The charge and discharge specific capacities after 100 cycles are 65.95 mAh / g and 64.88 mAh / g, respectively, and the coulombic efficiency is 98.38%. The discharge specific capacity retention rate at the 100th cycle is 94.78%. The results show that the hygroscopic sodium ferrous sulfate positive electrode material is directly sintered without adding a gas generating agent in the comparative example of the present invention. Although its cycle performance is restored, its discharge specific capacity is reduced, indicating that when the dehumidification treatment is carried out without the presence of a gas generating agent, Na2 Fe(SO 4 ) 2 •4H 2 O crystal hydrates hinder the sodium ion deintercalation channel and affect the material properties.

[0067] Comparative Example 2 5.48 g of the sodium-containing 2 Fe(SO 4 ) 2 ·4H 2 The hygroscopic sodium ferrous sulfate positive electrode material of O and 0.055g sodium oxalate are ground and mixed at a rotation speed of 120r / min for 8min until uniform. The obtained mixed powder is placed in a corundum crucible and placed in a tubular furnace. In a high-purity nitrogen atmosphere, the temperature is increased from room temperature to 450°C at a rate of 10°C / min, and then heat-treated for 2h. The mixture is cooled to room temperature with the furnace to obtain a dehumidified sulfate-based positive electrode material.

[0068] After testing, the morphology of the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention is micron-shaped spherical or fragmentary particles and agglomerates thereof, with a particle size range of 5 to 45 μm, wherein the particle sizes of D10, D50, and D90 are 6.053 μm, 20.234 μm, and 44.897 μm, respectively, that is, the particle size of the dehumidified sodium ferrous sulfate positive electrode material obtained by the comparative example of the present invention is between the particle size of the sodium ferrous sulfate positive electrode material before and after moisture absorption, indicating that after the dehumidification treatment of the comparative example of the present invention, the water molecules on the surface of the positive electrode material cannot be completely removed.

[0069] After testing, the hygroscopic sodium ferrous sulfate positive electrode material of the comparative example of the present invention was sintered at high temperature, and the crystal structure of the sodium ferrous sulfate collapsed. 2.5 Fe 1.75 (SO 4 ) 3 The peak shapes of the samples were compared with those of the standard card (PDF#97-025-2404), but the correspondence was not perfect.

[0070] The positive electrode sheet made of the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention is used to assemble a button-type sodium ion battery.

[0071] The preparation method of the positive electrode plate is the same as that of Example 1.

[0072] The battery assembly method is the same as in Example 1.

[0073] After testing, the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention has a charge and discharge voltage of 2.0 to 4.5 V and a rate of 0.1C (11 mA / g), and the first charge and discharge specific capacities are 65.33 mAh / g and 61.65 mAh / g, respectively, and the coulombic efficiency is 94.37%; the results show that the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention, although its electrochemical performance still has a numerical value, the performance parameters are not good, indicating that dehumidification treatment outside the temperature range specified by the method of the present invention will cause the material to decompose and does not have ideal electrochemical performance.

[0074] After testing, the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention has a discharge specific capacity of 58.22 mAh / g starting from the 4th cycle at a charge and discharge voltage of 2.0 to 4.5 V and a rate of 1C (110 mA / g). The charge and discharge specific capacities after 100 cycles are 58.45 mAh / g and 54.97 mAh / g, respectively. The coulombic efficiency is 94.05%, and the capacity retention rate at the 100th cycle is only 89.16%. The results show that the dehumidified sodium ferrous sulfate positive electrode material obtained in the comparative example of the present invention has poor electrochemical properties, indicating that when the dehumidification treatment is carried out outside the temperature range specified by the method of the present invention, the decomposition of the material will cause the crystal structure to deform, thereby resulting in the loss of some electrochemical properties.

Claims

1. A method for dehumidifying a hygroscopic sulfate-based cathode material, characterized in that: The hygroscopic sulfate-based cathode material and the gas generating agent are uniformly mixed, heat-treated in an inert atmosphere, and cooled to room temperature along with the furnace to obtain a dehumidified sulfate-based cathode material.

2. The dehumidification method of the hygroscopic sulfate-based cathode material according to claim 1, characterized in that: The amount of the gas generating agent is 0.1-5.0% of the mass of the hygroscopic sulfate-based positive electrode material; the gas generating agent includes: one or more of glucose, sucrose, ascorbic acid, citric acid, sodium bicarbonate, sodium acetate, sodium oxalate or ammonium carbonate.

3. The method for dehumidifying a hygroscopic sulfate-based cathode material according to claim 1 or 2, characterized in that: The hygroscopic sulfate-based positive electrode material before and after moisture absorption includes a sulfate-based positive electrode material having a molecular formula of A 2+2x M 2-x (SO4)3 compound and its carbon coating material, wherein 0≤x≤0.3; the hygroscopic sulfate-based positive electrode material contains a crystalline hydrate with the molecular formula A2M(SO4)2·yH2O and its carbon coating material, wherein 1≤y≤9; the moisture content of the hygroscopic sulfate-based positive electrode material is 1-30%; A in the sulfate-based positive electrode material or the hygroscopic sulfate-based positive electrode material molecular formula represents Na or Li, and M represents a divalent transition metal; the morphology of the hygroscopic sulfate-based positive electrode material is micron-shaped spherical or fragment-shaped particles and their agglomerates; the particle size range of the hygroscopic sulfate-based positive electrode material is 1-50μm.

4. The method for dehumidifying a hygroscopic sulfate-based cathode material according to any one of claims 1 to 3, characterized in that: The mixing method includes grinding, sand milling or ball milling; the mixing speed is 120-180 r / min and the mixing time is 1-10 min.

5. The method for dehumidifying a hygroscopic sulfate-based cathode material according to any one of claims 1 to 4, characterized in that: The heat treatment refers to: heating from room temperature to 100-400° C. at a rate of 1-10° C. / min, and then keeping the temperature for 1-24 hours; the inert atmosphere includes one or more of argon, helium or nitrogen.